PERLINDUNGAN HUKUM KESELAMATAN DAN KESEHATAN BAGI PEKERJA PADA ERA NEW NORMAL PANDEMI COVID-19 - hartanto SE hartanto (Fakultas Hukum Universitas Riau, 2021)
Workers are a valuable asset in the development of the nation's economy who are obliged to receive occupational safety and health protection. The implementation of occupational safety and health aims to provide protection for workers to be healthy, safe, productive, and avoid occupational accidents and occupational diseases. In a new normal state, the demands for health protection must be really emphasized and must comply with the standard health protocol for the response to the Covid-19 pandemic.The formulation of the problem is what is the role of the state and employers in the framework of protecting occupational health and safety during the new normal covid pandemic 19? What are the forms of occupational health and safety protection for workers in the new normal period? This research is a legal research that uses several approaches to be able to answer the problems under study, namely the statute approach, and the conceptual approach, and using the content analysis method.The role of the state in the framework of protecting occupational health and safety during the Covid-19 pandemic is due to public relations, which automatically creates legal consequences in the form of public rights and obligations between the state and citizens. The role of the employer in providing protection for workers arises because the employer and the worker are bound by a private legal relationship, one of whose rights and obligations are related to the protection of occupational safety and health. The forms of occupational health and safety protection for workers in the new normal period are aimed at protecting everyone who is in the workplace, so if the right to occupational health is not fulfilled, it will have legal consequences in both the civil, criminal and administrative realms.Keywords: occupational safety and health, legal protection, labor